The Effect of Problem-Based Learning Method on Students Writing Descriptive Text: Adisty Intan Bruneiwati*, Aswir, Mutiarani - Adisty Intan Bruneiwati; Aswir; Mutiarani (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2024)
Research on the influence of problem-based learning methods really needs to be carried out. This research aims to determine the effectiveness of the problem-based learning (PBL) method in improving students' writing skills. This research uses quantitative methods. This research was conducted with a quasi-experimental design involving two groups of students, one group received conventional teaching without treatment, while the other group received treatment in the form of PBL teaching. Data was collected through pre-test and post-test writing assessments, and the results were analyzed using a t-test. The research results showed that students who received teaching using the PBL method showed significant improvements in their writing skills compared to those who received conventional learning. This research concludes that PBL can be an effective method for improving students' writing skills by providing opportunities for real-world problem-solving, collaborative learning, and revision based on feedback.